2003
DOI: 10.1107/s0909049502017739
|View full text |Cite
|
Sign up to set email alerts
|

Interferometer-controlled scanning transmission X-ray microscopes at the Advanced Light Source

Abstract: Two new soft X-ray scanning transmission microscopes located at the Advanced Light Source (ALS) have been designed, built and commissioned. Interferometer control implemented in both microscopes allows the precise measurement of the transverse position of the zone plate relative to the sample. Long-term positional stability and compensation for transverse displacement during translations of the zone plate have been achieved. The interferometer also provides low-distortion orthogonal x, y imaging. Two different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
553
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 674 publications
(566 citation statements)
references
References 37 publications
7
553
0
1
Order By: Relevance
“…Promising advances for 3-D analysis of collected samples have been made using techniques such as scanning transmission X-ray microscopy (STXM). 197 Fig . 8, for example, shows a plot of the relative amounts of carboxylic acid groups as a function of distance from the center of the particles collected in Mexico City.…”
Section: Oxidation Of Surface Organicsmentioning
confidence: 99%
“…Promising advances for 3-D analysis of collected samples have been made using techniques such as scanning transmission X-ray microscopy (STXM). 197 Fig . 8, for example, shows a plot of the relative amounts of carboxylic acid groups as a function of distance from the center of the particles collected in Mexico City.…”
Section: Oxidation Of Surface Organicsmentioning
confidence: 99%
“…The most advanced STXMs presently use laser interferometers to reduce the effect of imperfections in sample positioning during NEXAFS scans (Kilcoyne et al, 2003). High-precision mirrors attached to the sample and the zone plate mount reflect parts of a divided laser beam.…”
Section: Nexafs Techniques and Instrumentationmentioning
confidence: 99%
“…The microscope is described in detail elsewhere. 11 This beamline is equipped with an EPU source, which enables the selection of both linearly and circularly polarized light. We always used linearly polarized light, and rotated the photon polarization vector in a 90°range.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…8,9 Dichroism in carbonates generates a polarizationdependent imaging contrast (PIC), which is particularly useful to investigate the meso-scale architecture of nacre using X-ray photoelectron emission spectromicroscopy (X-PEEM) 10 and scanning transmission X-ray spectromicroscopy (STXM). 11,12 With X-PEEM we revealed that the 400-nm high, 5-µm wide aragonite tablets that form the layered abalone nacre structure are arranged in stacks of co-oriented tablets, staggered with respect to each other.We have previously extensively characterized the origin of PIC and X-ray linear dichroism with a series of pure- …”
mentioning
confidence: 95%